2011
DOI: 10.1021/bi200549x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustically Mounted Microcrystals Yield High-Resolution X-ray Structures

Abstract: We demonstrate a general strategy to determine structures from showers of microcrystals. It uses acoustic droplet ejection (ADE) to transfer 2.5 nanoliter droplets from the surface of microcrystal slurries, through the air, and onto mounting micromesh pins. Individual microcrystals are located by raster-scanning a several micron X-ray beam across the cryocooled micromeshes. X-ray diffraction datasets merged from several micron-sized crystals are used to solve 1.8 Å resolution crystal structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…However, droplet speeds produced tend to be unstable on the necessary timescales, making synchronization difficult. Additional challenges faced by this method include large droplet size and thus high background 96,97 , crystal settling without the addition of a viscous solution 48 , and compatibility with high vacuum 48 . To date, neither the pulsed liquid jet nor acoustic droplet ejection has been employed at an XFEL successfully.…”
Section: Sample Delivery Methodsmentioning
confidence: 99%
“…However, droplet speeds produced tend to be unstable on the necessary timescales, making synchronization difficult. Additional challenges faced by this method include large droplet size and thus high background 96,97 , crystal settling without the addition of a viscous solution 48 , and compatibility with high vacuum 48 . To date, neither the pulsed liquid jet nor acoustic droplet ejection has been employed at an XFEL successfully.…”
Section: Sample Delivery Methodsmentioning
confidence: 99%
“…While capillary and microfluidic devices can clog and damage crystals by subjecting them to shear force, in ADE the droplet emerges from the meniscus of the fluid without passing through an orifice. Some current applications of ADE in macromolecular crystallography (MX) include crystal growth (Villaseñor et al, 2012), microseeding (Villaseñor et al, 2010), ligand screening (Cole et al, 2014; Teplitsky et al, 2015; Yin et al, 2014), and discrete crystal deposition onto data collection media for synchrotron-based cryo-crystallography (Cuttitta et al, 2015; Heroux et al, 2014; Roessler et al, 2013; Soares et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that protein crystals can be harvested by using acoustic droplet ejection (ADE) to propel small droplets containing crystals out of the mother liquor, through a short air column, and onto a micromesh 1 or onto a crystal transporting conveyor belt that is linked to the x-ray diffractometer. using sonar is modest compared with other techniques.…”
Section: Introductionmentioning
confidence: 99%